Serum vitamin E levels and chronic inflammatory skin diseases: A systematic review and meta-analysis - Liu, Xiaofang; Yang, Guang; Luo, Mengxin; Lan, Qi; Shi, Xiaoxia; Deng, Haoyuan; Wang, Ningning; Xu, Xuezhu; Zhang, Cong (PLOS ONE, 2021)
Background Vitamin E has long been linked to skin health, including all of its possible functions in cosmetic products, to its roles in membrane integrity and even the aging process. However, reports on the relationship between serum vitamin E levels and the risk of chronic inflammatory skin diseases have been inconsistent. We performed a systematic review and meta-analysis to evaluate the association between serum vitamin E levels and chronic inflammatory skin diseases. Methods We searched the PubMed, Web of Science and Scopus databases, with no time limit up to 30.06.2021. Studies examining serum vitamin E levels in patients with chronic inflammatory skin diseases were selected. Results Twenty articles met the inclusion criteria. Compared with controls, a lower vitamin E level was found in patients with vitiligo (SMD: -0.70, 95% CI: -1.21 to -0.19), psoriasis (SMD: -2.73, 95% CI: -3.57 to -1.18), atopic dermatitis (SMD: -1.08, 95% CI: -1.80 to -0.36) and acne (SMD: -0.67, 95% CI: -1.05 to -0.30). Conclusions Our meta-analysis showed that serum vitamin E levels were lower in patients suffering from vitiligo, psoriasis, atopic dermatitis and acne. This study highlights the need to evaluate vitamin E status to improve its level in patients with skin diseases.